Fish communities diverge in species but converge in traits over three decades of warming. (22nd August 2019) - McLean, Matthew; Mouillot, David; Lindegren, Martin; Villéger, Sébastien; Engelhard, Georg; Murgier, Juliette; Auber, Arnaud
Abstract: Describing the spatial and temporal dynamics of communities is essential for understanding the impacts of global environmental change on biodiversity and ecosystem functioning. Trait‐based approaches can provide better insight than species‐based (i.e. taxonomic) approaches into community assembly and ecosystem functioning, but comparing species and trait dynamics may reveal important patterns for understanding community responses to environmental change. Here, we used a 33‐year database of fish monitoring to compare the spatio‐temporal dynamics of taxonomic and trait structure in North Sea fish communities. We found that the majority of variation in both taxonomic and trait structure was explained by a pronounced spatial gradient, with distinct communities in the southern and northern North Sea related to depth, sea surface temperature, salinity and bed shear stress. Both taxonomic and trait structure changed significantly over time; however taxonomically, communities in the south and north diverged towards different species, becoming more dissimilar over time, yet they converged towards the same traits regardless of species differences. In particular, communities shifted towards smaller, faster growing species with higher thermal preferences and pelagic water column position. Although taxonomic structure changed over time, its spatial distribution remained relatively stable, whereas in trait structure, the southern zone of the North Sea shifted northward and expanded, leading to homogenization. Our findings suggest that global environmental change, notably climate warming, will lead to convergence towards traits more adapted for novel environments regardless of species composition. Abstract : We compared the spatio‐temporal dynamics of species and trait structure in North Sea fish communities over 33 years. Both species and trait structure changed significantly over time; however, communities in the southern and northern North Sea diverged towards different species, becoming taxonomically more dissimilar over time, yet they converged towards the same traits regardless of species differences. In particular, communities shifted towards smaller, faster growing species with higher thermal preferences and pelagic water column position. Our findings suggest that global environmental change, notably climate warming, will lead to convergence towards traits more adapted for novel environments regardless of species composition.